Handbook of Conspiracy Theory and Contemporary Religion 2018
DOI: 10.1163/9789004382022_006
|View full text |Cite
|
Sign up to set email alerts
|

Are Conspiracy Theories a Surrogate for God?

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Yet we contend that the substantive similarities between religious beliefs, spirituality, and support for conspiracy theories are negligible, making the argument unconvincing. By contrast, research in political psychology suggests that the observed correlations are explained by the fact that religious beliefs, conspiracy ideation, and other so-called epistemically unfounded beliefs (e.g., belief in the paranormal and pseudo-science) are rooted in individual differences in thinking styles especially with regard to information about potential transcendental realities (Baumard and Boyer, 2013;Lobato et al, 2014;Ståhl and van Prooijen, 2018;Wood and Douglas, 2018). Dual process theories of thinking distinguish between intuitive and holistic information processing styles (type 1) and more analytic and deliberative thinking (type 2) processes (Evans, 2008;Stanovich, 2010;Kahneman, 2012).…”
Section: Analytic Cognitive Style and Conspiracy Beliefsmentioning
confidence: 87%
See 3 more Smart Citations
“…Yet we contend that the substantive similarities between religious beliefs, spirituality, and support for conspiracy theories are negligible, making the argument unconvincing. By contrast, research in political psychology suggests that the observed correlations are explained by the fact that religious beliefs, conspiracy ideation, and other so-called epistemically unfounded beliefs (e.g., belief in the paranormal and pseudo-science) are rooted in individual differences in thinking styles especially with regard to information about potential transcendental realities (Baumard and Boyer, 2013;Lobato et al, 2014;Ståhl and van Prooijen, 2018;Wood and Douglas, 2018). Dual process theories of thinking distinguish between intuitive and holistic information processing styles (type 1) and more analytic and deliberative thinking (type 2) processes (Evans, 2008;Stanovich, 2010;Kahneman, 2012).…”
Section: Analytic Cognitive Style and Conspiracy Beliefsmentioning
confidence: 87%
“…Thus, holistic spiritualities and conspiracy beliefs are both at odds with established "truthmaking institutions" (Boyer, 2020, 87) and contest the domination of these institutions. Spiritual believers see themselves in opposition to the Christian mainline congregations that dominate the religious field, just as conspiracy believers see themselves in opposition to the mainstream worldviews with regard to their political attitudes, health beliefs, and behaviors (Lamberty and Imhoff, 2018;Wood and Douglas, 2018). Scholars of conspiracy beliefs argue that this similarity explains the higher disposition of spiritual believers toward conspiracy beliefs because of their deeply rooted conviction of having insights into the truth of hidden power structures (Robertson and Dyrendal, 2018).…”
Section: Religion Spirituality and Conspiracy Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is from these complex social processes, we conjecture, that much of the phenomenon of conspiratorial thinking emerges. While these ideas have not been directly proposed or tested, related notions can be found in research hypothesizing that conspiracy theories substitute for religion and that conspiracy communities share many features with religious communities (Franks, Bangerter, & Bauer, 2013; Wood & Douglas 2018). The study of the social nature of conspiracy communities has gained recent scholarly attention among sociologists interested in social movements, but this work is still in its infancy (Bertuzzi, 2021).…”
Section: Understanding Conspiracy Theories: Three Levels Of Analysismentioning
confidence: 99%